Republic of Korea : Financial Sector Assessment Program-Detailed Assessment of Compliance on the CPSS-IOSCO Principles for Financial Market Infrastructures?BOK-WIRE+ and KRX CPP. (IMF Staff Country Reports; Country Report ;, 2014)
EXECUTIVE SUMMARY Korea has a well-developed payment, clearing, and settlement infrastructures. BOK-WIRE+ is the real-time interbank gross payment and settlement system, and the backbone of the infrastructure where the final payments of various markets are settled. It is operated by the Bank of Korea (BOK). The Korea Exchange (KRX) is the main player in the securities and derivatives market, operating three exchanges and offering clearing and settlement services for all securities and derivatives traded on the KRX. While the authorities have decided to establish a central counterparty (CCP) for over-the-counter (OTC) derivatives at a future date, discussions are ongoing on the desirability of transforming the current trade reporting systems into full-fledged trade repositories (TRs). The planned CCP for OTC derivatives should ensure full compliance with the Principles for Financial Market Infrastructures (PFMI) before being launched, taking into account lessons learned from the assessment of the CCP for exchange-traded products. BOK-Wire+ is largely compliant with the PFMI, and is overall sound. It is subject to comprehensive and transparent risk management frameworks comprising clear policies and guidelines, governance arrangements, and operational systems including regularly tested default and business continuity procedures. All transactions once settled in BOK-Wire+ are deemed final and irrevocable, as well as bankruptcy remote. There is room for improvement in certain areas to enhance the level of compliance of the BOK-Wire+ with the PFMI. It is recommended that the operator of BOK-Wire+ improves the collateral risk management framework by adopting regular testing of haircuts and an independent validation of haircut procedures at least annually. The BOK should provide more clarity in the regulations regarding settlement finality and queue management, particularly with regard to revocation of queued transactions. It should also fully implement the disclosure framework, including disclosure of relevant rules and regulations in English. Finally, BOK's oversight powers should be strengthened, to include linked financial market infrastructures (FMIs) and participants, particularly to obtain authentic information and enforce compliance.